Patologia - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
Research on plant pathology carried out during 1981 emphasized the study of some epidemiological, etiological, and physiological factors related to the occurrence of the superelongation disease of cassava caused by Sphaceloma manihoticola. Dry-heat treatments (60 degrees Celsius for 14 days) breaks seed dormancy and controls the pathogen Xanthomonas campestris pv. manihotis, causal agent of CBB. Etiological factors of the frog skin disease were studied through spectrophotometric and electrophoretic analysis of concentrated extracts of infested cassava tissues. The presence of nucleoproteins and proteins not present in healthy plant tissues was revealed. Similar studies to identify the causal agent of the Caribbean cassava mosaic, observed in the northern coast of Colombia, detected an UV absorption curve typical of a nucleoprotein although no virus-like particles were observed. Other diseases studied include those caused by Choanephora curcubitarum, Colletotrichum manihotis, C. gloeosporioides, and Diplodia. Studies on biotic problems in 5 different edaphoclimatic zones in Colombia were continued as well as the studies on susceptibility of cv. topostharvest physiological deterioration. (CIAT)